IT security advice from experts - Oliva, Lawrence M.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
Increasing every day in frequency and sophistication, planned cyber attacks are impacting systems, data and user access at virtually every business and government organization. Whether accidentally triggered by users opening their daily e-mail, or planned denial of services attack triggering a thousand zombie systems, IT management and corporate executives must be ready to respond, minimize and defeat threats to revenue generating and citizen facing operations. In many cases, the decision to protect information assets may materially impact agency or corporate budgets, previously planned investment and projected shareholder returns.
1. Executive overview/ Lawrence M. Oliva -- Section I. Governance issues -- 2. Aligning assurance requirements, countermeasures, and business / Craig E. Kaucher -- 3. Protecting customer provided information / Charles Rex IV -- 4. Global IT risk management strategies / Chrisan Herrod -- Section II. Architecture issues -- 5. Architecture issues / Lawrence M. Oliva -- Section III. Technology issues -- 6. Wireless information security / Clifton Poole -- 7. Reference materials -- About the authors -- Index.
Includes bibliographical references (p. 152-165) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 26, 2010).
Keywords: Computer security; Electronic books